Finance and the improved cookstove sector in East Africa: barriers and opportunities for value-chain actors - Hewitt, Joseph; Ray, Charlotte; Jewitt, Sarah; Clifford, Mike (Elsevier, 2018)
Despite a long history of diverse approaches designed to increase the adoption of improved cookstoves (ICS), multiple barriers continue to exist which stunt their uptake in many developing countries. This paper focuses specifically on the financial barriers facing actors within the ICS value chain, such as manufacturers, suppliers and distributors. Examining data from interviews with twenty nine ICS enterprises in Kenya and Uganda, this paper finds that limited access to credit services is a substantial barrier to increasing the capacity of businesses within the ICS value chain. In addition, data from twenty-seven financial providers including banks, microfinance institutions and savings and credit co-operatives (SACCOs) viewed the ICS market as relatively underserved and believed greater integration could be mutually beneficial. This paper explores the way in which this relationship plays out in current market conditions and how connections between the two sectors can be strengthened, with the objective of overcoming these financial challenges and expanding the capacity of ICS businesses as a mechanism to facilitate ICS uptake by local populations.